In Vitro Symbiotic Germination: A Revitalized Heuristic Approach for Orchid Species Conservation - Galih Chersy Pujasatria; Chihiro Miura; Hironori Kaminaka (Plants, 2020)
As one of the largest families of flowering plants, Orchidaceae is well-known for its high diversity and complex life cycles. Interestingly, such exquisite plants originate from minute seeds, going through challenges to germinate and establish in nature. Alternatively, orchid utilization as an economically important plant gradually decreases its natural population, therefore, driving the need for conservation. As with any conservation attempts, broad knowledge is required, including the species’ interaction with other organisms. All orchids establish mycorrhizal symbiosis with certain lineages of fungi to germinate naturally. Since the whole in situ study is considerably complex, in vitro symbiotic germination study is a promising alternative. It serves as a tool for extensive studies at morphophysiological and molecular levels. In addition, it provides insights before reintroduction into its natural habitat. Here we reviewed how mycorrhiza contributes to orchid lifecycles, methods to conduct in vitro study, and how it can be utilized for conservation needs.